An exploratory multi-indicator assessment of freshwater ecosystem health in two South African reservoirs - Zamantungwa Thobeka Happiness Mnisi; Minah Mmakgonchane Matheta; Collins Nkotoloane Mashilwane; Willem Johannes Smit; Kedibone Masenya; Wilmien Jacoba Luus-Powell (Aquatic Ecology, 2026)
This study assessed freshwater ecosystem health by integrating chemical, biological, and microbial indicators. We conducted an exploratory comparison of Loskop Dam and Nwanedi-Luphephe Dam, South Africa, using water quality parameters, fish Health Assessment Index (HAI) scores, parasite assemblages, and 16S rRNA gut microbiota profiling. Sampling occurred between March and May 2025. Selected water parameters were measured in situ, with nutrient and metal analyses conducted from 1 L water samples. Nineteen fish ( Oreochromis mossambicus , n = 10; Clarias gariepinus , n = 9) were examined for parasites, and gut microbial communities and the HAI scores calculated. The microbial functional prediction potential was inferred using PICRUSt2. Loskop Dam showed elevated total dissolved solids (272.75 mg/L vs. 40 mg/L), conductivity (41.07 vs. 6.0 mS/m), and pH (7.69 vs. 7.14) values compared with Nwanedi-Luphephe Dam. Fish from Loskop Dam exhibited a higher mean HAI score (45.0 ± 25.50) than Nwanedi-Luphephe Dam (34.4 ± 14.24) and greater endoparasite loads, particularly Contracaecum spp. , whereas fish from Nwanedi-Luphephe Dam harboured more ectoparasitic monogeneans. Gut microbiota was dominated by the phyla Fusobacteriota, Bacillota, Pseudomonadota and Planctomycetota, while classified genera were primarily represented by Cetobacterium, Romboutsia, Clostridium, Bacteroides and Sediminibacterium . In the final multivariable model, fish weight was the only significant predictor of HAI score (p = 0.03), whereas dam and fish species were not significant. PICRUSt2 identified ten metabolic pathways differing between dams, with nine core pathways enriched in Nwanedi-Luphephe Dam; PWY01479, PWY042, PWY-5747, PWY-5856, PWY-5857, PWY-5855, PWY-6708, UBISYN-PWY, and PWY-5920, while the nucleotide salvage pathway (PWY-6609) was enriched in Loskop Dam. Results reveal that Loskop Dam exhibits moderate anthropogenic impact, whereas Nwanedi-Luphephe Dam represents a relatively undisturbed ecosystem. Integrating water chemistry, fish health, parasite assemblages, and gut microbiota may offer a sensitive framework for monitoring freshwater ecosystem integrity and detecting early ecological disturbance.

Factors predicting incidence of nontuberculous mycobacteria in an era of climate change and altered ecosystems in the United States - Samantha J. Bents; Collin Powell; Joshua P. French; D. Rebecca Prevots; Rachel A. Mercaldo (Science of The Total Environment, 2025)

Dietary reconstruction based on stable isotopes and stature at Torre de Palma, a Late Roman/Late Antiquity site in southern Portugal - Mark R. Schurr; Mary Lucas Powell; Della Collins Cook; Michael MacKinnon; Maia M. Langley (Archaeological and Anthropological Sciences, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)